A Case Report of Neurotoxicity After Prolonged Doses of Acyclovir in a Patient With Renal Dysfunction. (April 2020) - Umoru, Godsfavour O.; Shah, Punit J.; Tariq, Farheen
Renal dysfunction is a significant risk factor for acyclovir-induced neurotoxicity and altered mentation and myoclonic movements are the most common clinical symptoms observed. In majority of reported cases, neurological sequelae associated with acyclovir-induced neurotoxicity often mimic viral infections of the central nervous system and makes diagnosis of the former challenging. Although plasma concentrations of the drug may not always correlate with neurotoxic symptoms, obtaining serum levels of acyclovir may be helpful in confirming drug-induced neurotoxicity. Hemodialysis has been shown to significantly improve altered mentation in patients with suspected or confirmed acyclovir-induced neurotoxicity. Here, we report a definite case of acyclovir-induced neurotoxicity in a patient with end-stage renal disease. Clinical improvements in neurologic symptoms were observed following discontinuation of the drug and hemodialysis.